Using Information Technology to Quantitatively Evaluate and Prevent Cybersecurity Threats in a Hierarchical Manner - Mai, Rui; Wu, Mingzhu (International Journal for Applied Information Management, 2023)
The vulnerability of traditional network security technology in the face of rapid advancements in information technology and the constant changes in network security. As a result, hackers can easily exploit loopholes in traditional security measures, such as cracking cryptographic algorithms, and stealing sensitive user information and data, which has led to a crisis of trust in recent years. To ensure safe and effective operation of massive data on the network, this article presents a quantitative assessment of the network's threat situation. The assessment is divided into two parts: support evaluation and credibility evaluation. These parts are further broken down into three levels of evaluation and severity evaluation. The article also provides a list of network security-related precautions that can be taken to mitigate potential risks. The experimental results show that implementing these hierarchical security measures can improve the security rate of Internet users' information by 4%-5%. Overall, the article highlights the importance of adopting more advanced and sophisticated security measures to combat the increasingly complex threats posed by cybercriminals.